Neo-Islamic culture's influence on recent Turkish media - Kotaman, Asli; Avcı, Artun; Cetrez, Önver A. (Cambridge Scholars Publishing, 2017)
The volume looks at the relation between contemporary Turkish film and television discourses and religion, in relation to the traditions and rituals of Islam, the representation of Muslim women, and subsequent changes in narratives and characters. It employs differing approaches to the relationships between media and religion, concentrating on how religion has started to shape the politics of film in new cinema practices in Turkey.